Pulsed power driven cylindrical wire array explosions in different media - Yanuka,D; Theocharous,S; Bland,SN (PHYSICS OF PLASMAS, 2019)
Cylindrical copper wire array explosions were carried out in de-ionized water, sodium polytungstate solution, nitromethane, and polyester in order to obtain high energy density conditions in the vicinity of implosion using the generated converging shock waves. The use of different materials in which the array is immersed can contribute to this goal with higher density resulting in higher shock velocities and possible combustion. The generated shock waves were captured by a framing and a streak camera, and shock velocities were calculated and compared. The pressure behind the shock front was calculated using the known hydrodynamic relations (for water, polytungstate, and polyester) and compared to two-dimensional hydrodynamic simulations coupled with the equations of state (for water and polyester). It was shown that despite lower shock wave velocity in polytungstate solution than in water, the pressures generated are similar in both materials. In polyester, both shock velocities and generated pressures are 2–4 times higher than in water. It was also shown that it is possible to carry out these explosions in a solid which has several advantages compared to liquids, such as not relying on waterproof systems and easier transportation.